2019
DOI: 10.3390/ijerph16193595
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette and E-Cigarette Use and Smoking Cessation Practices among Physicians in Poland

Abstract: Physicians play a key role in combating tobacco use. This study aims to evaluate the knowledge, attitude, and behaviors toward smoking cessation and vaping cessation interventions among physicians in Poland; to identify factors shaping physicians’ behaviors toward smoking and vaping cessation interventions; and to assess differences in the tobacco cessation interventions recommended for cigarette smokers and users of electronic cigarettes (e-cigarettes). A questionnaire-based survey was conducted in 2018 among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 48 publications
0
13
0
1
Order By: Relevance
“…Research by Jankowski et al has shown that doctors in Poland do not routinely intervene in the case of their patients. The study revealed that while 37.6% of physicians regularly offered smokers a minimum intervention to stop smoking, only 5% of physicians offered referrals to smoking cessation clinics [45].…”
Section: Discussionmentioning
confidence: 99%
“…Research by Jankowski et al has shown that doctors in Poland do not routinely intervene in the case of their patients. The study revealed that while 37.6% of physicians regularly offered smokers a minimum intervention to stop smoking, only 5% of physicians offered referrals to smoking cessation clinics [45].…”
Section: Discussionmentioning
confidence: 99%
“…Findings from the EUREST-PLUS ITC Europe Surveys revealed that the percentage of smokers who receive professional advice to quit varies from 57% in Romania to 21% in Poland [32]. Several studies revealed that physicians in CEE Europe do not routinely identify a patient's smoking status and do not offer smoking cessation treatment to patients who smoke [32][33][34]. Currently there is a lack of up-to-date data on smoking cessation attempts among smokers from non-EU member countries in Eastern Europe.…”
Section: Discussionmentioning
confidence: 99%
“…As indicated by the increase in cigarette prices by 10%, the decrease in consumption in Bulgaria, Romania and Poland would be affected [61]. Given that the use of tobacco products is widespread in Poland, including in the medical profession [62], it cannot be assumed that the effective component limiting the use of tobacco products are the legal provisions relating to this issue. The provisions of the Tobacco Control Act provide an illusory basis for the protection of health and the rights of non-smokers.…”
Section: Resultsmentioning
confidence: 99%